A MIXED INTEGER LINEAR PROGRAMMING FORMULATION FOR LOW DISCREPANCY CONSECUTIVE K-SUMS PERMUTATION PROBLEM - BOGDANOVI´Ć, Milena; MAKSIMOVIĆ, Zoran; SIMIĆ, Ana; MILOŠEVIĆ, Jelisavka (Yugoslav Journal of Operations Research; Vol 27 No 1 (2017), 2016)
In this paper, low discrepancy consecutive k-sums permutation problem is considered. A mixed integer linear programing (MILP) formulation with a moderate number of variables and constraints is proposed. The correctness proof shows that the proposed formulation is equivalent to the basic definition of low discrepancy consecutive k-sums permutation problem. Computational results, obtained on standard CPLEX solver, give 88 new exact values, which clearly show the usefulness of the proposed MILP formulation.